THE GENEALOGY OF MUSLIM RADICALISM IN INDONESIA: A Study of the Roots and Characteristics of the Padri Movement (JOURNAL OF INDONESIAN ISLAM, 2008)
This paper will trace the roots of religious radicalism in Indonesia with the Padri movement as the case in point. It argues that the history of the Padri movement is complex and multifaceted. Nevertheless, it seems to be clear that the Padri movement was in many ways a reincarnation of its counterpart in the Arabian Peninsula, the Wahhabi movement, even though it was not a perfect replica of the latter. While the two shared some similarities, they were also quite different in other respects. The historical passage of the Padris was therefore not the same as that of the Wahhabis. Each movement had its own dimensions and peculiarities according to its particular context and setting. Despite these differences, both were united by the same objective; they were radical in their determination to establish what they considered the purest version of Islam, and both manipulated religious symbols in pursuit of their political agendas.